Biocompatibility of three-dimensional thermoplastic elastomer implants compared to that of the sternocephalic muscle flap in repairing partial tracheal defects in New Zealand white rabbits (Oryctolagus cuniculus) - Marcelo Carrijo da Costa; Ana Carolina Gasques Salgado dos Santos; Ariadne Rein; Gabriel Luiz Montanhim; Gustavo Fernandes; Luis Gustavo Gosuen Gonçalves Dias; Marcella Dall Agnol Leite; Nicolle Pereira Soares; Thiago André Salvitti de Sá Rocha; Marcelo Emilio Beletti; Paola Castro Moraes (Acta Cirúrgica Brasileira)
ABSTRACT Purpose: To evaluate the effectiveness and biocompatibility of a three-dimensional (3D) thermoplastic elastomer (TPE) prosthesis for repairing partial tracheal defects using 3D printing with fused deposition modelling. Methods: Thirty-two rabbits underwent partial resection of five tracheal rings and were divided into two groups: the muscular flap group (GFM), which received a sternocephalic muscle flap over the defect; and the TPE group (GTPE), which received a 3D-printed TPE prosthesis. Clinical evaluations were performed at seven, 15, 30, and 60 days postoperatively. Results: Cough was significantly more frequent in the GFM group (p = 0.035). Thermography showed no significant differences in surgical site temperatures between groups or time points. Tracheoscopy revealed more intraluminal secretions in the GTPE group (p = 0.006) and more exuberant tissue formation in the GFM group (p = 0.001). Complete epithelialization was observed in the GFM group after 60 days. Conclusion: The 3D TPE prosthesis demonstrated tissue compatibility and viability as an implant for partial tracheal defects, with minimal respiratory complications during the 60-day evaluation period.